Occupational Stress Among Faculty Members at Dental Universities in Tehran : Occupational Stress among Faculty Members - Valian, Azam; Najafi-Abrandabadi, Ahmad; aber Ansari, Zahra; Bahreinian, Seyed Abdolmajid; Maeghool, Faezeh; Mohsenzadeh, Leila (Journal of Dental School, 2025)
Objectives: Determining the job (occupational or work-related) stress of dental school faculty members is necessary for planning to improve the quality of dental education and the health and oral health status of people in society. This study aimed to determine the job stress of dental school faculty members in Tehran. Methods: In this descriptive cross-sectional study, 167 faculty members of Islamic Azad, Tehran, Shahed, and Shahid Beheshti dental schools were selected by convenience sampling, and using Osipow’s Occupational Stress Inventory, their job stress in six fields was evaluated. Osipow’s Occupational Stress Inventory was scored on a 5-point Likert scale from 1 to 5. Each phrase was rated on a scale from 1 to 5, with 1 indicating 'never' and 5 indicating 'most of the time.' The data were analyzed using t-test, Kruskal-Wallis, and ANOVA. Results: Most faculty members of dental schools in Tehran experienced low to moderate job stress across various fields. 60% had low-moderate job stress in the role workload, 75.3% in the role inadequacy,42.6% had low-moderate job stress in the role dichotomy, 59.4% had low-moderate job stress in the range of the job,73.2% had low-moderate job stress in the responsibility and 45% ad low-moderate job stress in all fields. A significant difference was between the age of faculty members and job stress in the range of jobs; with increasing age, job stress in this field was reduced. No significant difference was found in job stress scores according to gender and marital status, academic rank, or department of activity among faculty members of dental schools in Tehran. Conclusion: Most faculty members of dental schools in Tehran reported low-moderate job stress in most fields. The highest job stress was observed in the role workload, and the lowest was in the physical environment.